Daily full spectrum light exposure prevents food allergy-like allergic diarrhea by modulating vitamin D3 and microbiota composition - Po-Jung Chen (Nature Portfolio, 2021)
Abstract The importance of sun exposure on human health is well recognized, and a recent trend in the avoidance of sun exposure has led to the risk of missing the beneficial effects such as vitamin D3 biogenesis. Vitamin D3 insufficiency is one of the risk factors for the development of food allergies (FAs), and vitamin D3 status controls gut homeostasis by modulating the microbiota. This study aimed to explore the impact of daily full spectrum light exposure (phototherapy) on the pathogenesis of FAs. Phototherapy ameliorated allergic diarrhea and improved FA-associated vitamin D3 insufficiency and dysbiosis. Fecal microbiota transplantation (FMT) of FA donor feces induced allergic diarrhea with OVA-specific IgE elevation in naïve mice. In contrast, FMT of naïve donor feces ameliorated allergic diarrhea in established FA mice, suggesting the involvement of the microbiota composition in FA. Phototherapy is an alternative approach for the prevention of FA-like allergic diarrhea through the modulation of vitamin D3 status and microbiota composition.